Risk analysis of sulfur dioxide (SO2) exposure to public health around Kolaka district nickel processing plant - Azis, Sheril Dribisce; Azizah, R.; Jalaludin, Juliana (Airlangga University Faculty of Public Health, 2024)
Introduction: Sulfur dioxide (SO2) is an air pollutant that is mostly sourced from burning fossil fuels. Data from the Pomalaa Health Center in 2019 indicates a high incidence of Acurate Respiratory Infection (ARI), with 1,943 reported cases. This study aims to assess the respiratory health risk for communities near the nickel processing plant in Pomalaa District. Methods: This research employs an observational cross-sectional design alongside Environmental Health Risk Analysis (EHRA), the study sampled 122 out of 13,207 respondents using simple random sampling. The analysis was carried out with the kolmogorov-smirnov test and EHRA. Results and Discussion: EHRA results show an inhalation rate of 0.63 m3/hour, with an exposure time of 24 hours/day, an exposure frequency of 365 days/year, and exposure durations of 25 years for real-time projections and 30 years for lifetime projections. SO2 levels have surpassed national quality standards, with the highest concentration recorded at Point 4, measuring 0.576 mg/m3. Dose-response analysis, based on US-EPA data, indicates a level of 0.21 mg/m3. The average intake value for real-time exposure is 0.081 mg/kg/day, and the average intake value for 30-year lifetime is also 0.081 mg/kg/day. Kolmogorov-smirnov test results show a p-value of 0.200 for body weight, while p-values for exposure duration, exposure time, exposure frequency, SO2 concentration, intake rate, age group, intake value, and RQ are all 0.000. Conclusion: Most respondents in this study had health risks that were within safe limits. Nickel processing plant companies and local governments should conduct regular monitoring and control emissions from mining activities, including SO2.